CampusTrace- Application for Lost and Found Items on Campus - T, Abhiram; EB, Ashok Krishnan; KM, Manjith; AP, Vishnu; A, Ambarish (Journal of Trends in Computer Science and Smart Technology, 2024)
CampusTrace transforms the systems of lost and found items in campus environments by improving the process of reporting lost or found items and ensures the proper returns of the item to its rightful owners. It enhances social responsibility by encouraging people to collaborate with their owners in recovering the lost. Due to its user-friendly design, Campus Trace simplifies the process of searching for lost items and increases recovery efficiency by giving users a good user experience. The system offers several privacy methods in securing user data and requires admin authentication for item claims. This platform makes it not only easier to recover your lost things but also add cooperation and engagement within the campus community.